Enhancing Meaning in Learning: A Case Study of Adult Developmental Mathematics - Tim Glasser (Adult Education Research Conference, 2010)
This case study, at the focal site of the Art Institute of San Francisco, involves a yearlong study of adult developmental mathematics courses influenced by vocational instructor feedback and meaningful learning theory. Learner surveys on learning outcomes show negative learning progress compared to a national database of similar developmental courses. This contradicts the general hypothesis that meaning in instruction and learning correlate with successful learning outcomes. It may be that due to a history of rote learning and mathematical frustration, some adult learners show signs of cognitive overload on constructivist tasks.